Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Indra Bastian (Faculty of Economic & Business Universitas Gadjah Mada, 2014)
No. Penulis --- Judul Artikel --- Halamanrn1. Berto Usman and Eduardus Tandelilin --- Internet Search Traffic and Its Influence on Liquidity and Returns of Indonesia Stocks : An Empirical Study --- 203-221rn2. Muhammad Yunanto and Henny Medyawati ---- Monetary and Fiscal Policy Analysis : Which is More Effective? --- 222-236rn3. Sri Haryati and Emanuel Kristijadi --- The Effect of GCG Implementation and Risk Profile on Financial Performance at Go-Public National Commercial Banks --- 237-250rn4. Eko Suwardi, Arika Artiningsih and M. Ridwan Novmawan --- Student Perception on Business Ethics ---- 251?258rn5. Wihana Kirana Jaya, Anggi Rahajeng, and Indra Bastian Williamson --- Model : An Application of Institutional Transformation in the Indonesian DGT --- 259-272rn6. Muhammad Ryan Sanjaya --- Teaching of Behavioral and Experimental Economics and the Prospects for Teaching It in Developing Countries : A Survey --- 273-282rn7. Sumiyana ---- Book Review : Islam and the Moral Economy : The Challenge of Capitalism --- 283-286